Enabling voltage dip ride-throughs of large electric driven gas compressors. (February 2019) - Cortinovis, Andrea; Mercangöz, Mehmet; Besselmann, Thomas; Ditlefsen, Arne-Marius; Stava, Tor Olav; de moortel, Sture Van; Lunde, Erling
Highlights: Transient gas compressor modeling for estimating process state trajectories. Dynamic time to surge computation using process and electrical measurements. Model predictive surge protection for safe under-voltage ride-throughs. Analysis of two under-voltage occurrences on an industrial-sized gas compressor. Abstract: This article is concerned with the impact of voltage or power dips on large electric driven gas compressors (EDC) in typical oil and gas applications. EDCs are sensitive to voltage dips affecting the operation of the gas compression process through the complete or partial loss of motor torque. These events result in unpredictable shutdowns and plant trips typically leading to large economic losses in production. The loss of motor torque often puts the process at risk of surge conditions resulting in unstable operating conditions and possibly also in severe damage of the centrifugal compressors and their surrounding equipment. The critical nature of this problem and the fast dynamics involved, pose challenging requirements for the control and safety systems of the gas compressor and the variable-speed drive system. The main aim of the present paper is to present a model-based protection algorithm to safely decide if the EDC can ride-through or needs to be shutdown during voltage dips. This is done by dynamically computing the time to surge using online information from the process, from the electrical system and a process model to predict the behavior of the compression system. The time to surge value is then compared to a safety limit in order to reach a ride-through or shut-down decision. The approach is tested in simulation and after the deployment on an industrial sized compressor, two recorded voltage dips from the field are presented and discussed.